BARGAINING FAILURES AND MERGER POLICY. (August 2015) - Burguet, Roberto; Caminal, Ramon
<x xml:space="preserve">Abstract</x> We study approval rules in a model where horizontal merger proposals arise endogenously as the outcome of negotiations among the firms in the industry. We make two main points. First, relatively inefficient merger proposals succeed with positive probability. That is, the negotiation process may result in a particular merger agreement despite the existence of an alternative one that would generate higher profits and higher consumer surplus. Second, the antitrust authority should optimally commit to an approval rule that is more stringent for all mergers than the optimal ex post rule.